Cerebral Hemorrhage - Zhou, Liang-Fu; Xi, Guohua; Chen, Xian-Cheng; Keep, Richard F.; Huang, Feng-Ping; Hua, Ya; Lu, Yi-Cheng; Muraszko, Karin (Acta Neurochirurgica Supplement, 2008)
Cerebral hemorrhage is a common and often fatal subtype of stroke. while in the past it has received relatively little attention compared to ischemic stroke, there have been major advances in our understanding of this devastating form of stroke. The papers by world experts cover the field from molecular biology to clinical trials.